Are there barriers to independent non-executive directors' effectiveness in performing their roles? - Annuar, Hairul Azlan (Emerald, 2012)
Purpose – The purpose of this paper is to ascertain whether non-executive directors (NEDs) in Malaysian public listed companies (PLCs) may be facing certain barriers in the performance of their roles. Design/methodology/approach – A qualitative approach, consisting of a series of interviews with board members, was chosen. The sampling frame was made as large as possible and for the purpose of this study, consisted of board members who sit on the main board of Malaysian-owned PLCs. Findings – The interviews revealed that a majority of the interviewees perceived that the barriers were either non-existent or at least manageable. There were indications however that NEDs in small firms might face some of the problems suggested. The culture effect may also mediate their effectiveness in performing their roles. When there are barriers present, the most difficult problem faced by the NEDs concern time available to spend with the company. Research limitations/implications – This research utilized interviews. Generalizations may be an issue when interviews are used as the method of inquiry. Also, the sample is not random, as access to many directors depended on recommendations. In addition, respondents were consciously selected in order to obtain various board positions that include independent and non-independent directors. Practical implications – Findings from this research suggest that investors should not be overly concerned with their investments in Malaysian PLCs, as the NEDs are able to strongly discharge their responsibilities in overseeing executives’ conduct and protecting investors’ interest. The NEDs did not appear to face problems and hostilities from their host companies and it would be an added benefit to everyone concerned if they were able to more properly manage their time. Originality/value – There is a lack of work on studying barriers to NEDs’ effectiveness in developing countries, as previous work and literature reviews have been predominantly based upon the experience of Western economies.